Higher education in prisons: A historical analysis. - Crouse, Tara Elizabeth Ann. (University of Ottawa (Canada), 2000)
This thesis provides an exploration and analysis of university education in prisons from a historical point of view. It examines how post-secondary education in prisons has reproduced dominant economic and cultural relations, but also how it can resist doing this. A qualitative research process is used to investigate the empirical research produced in this field. The primary method used is the analysis of the experiences and the voices of persons who have participated in higher education in prisons as students and teachers. The primary objective is to give a voice to prisoners as a traditionally oppressed group. Past and current post-secondary education in Canadian prisons are examined, as are the problems encountered in both. An argument is made for an alternative form of education in prisons, with an emphasis on the pedagogy of Paulo Freire. Freire's work calls for the empowerment of the oppressed and argues that this is best done through participatory education. It is further argued that prisoners should be in charge of their own educational practices in order to counter the hegemony of correctional education's discourse.
Keywords: Education, Adult and Continuing.